Effect of Meal Texture on Postprandial Glucose Excursions and Gut Hormones After Roux-en-Y Gastric Bypass and Sleeve Gastrectomy - Hedbäck, Nora; Hindsø, Morten; Bojsen-Møller, Kirstine N.; Linddal, Adelaide K.; Jørgensen, Nils B.; Dirksen, Carsten; Møller, Andreas; Kristiansen, Viggo B.; Hartmann, Bolette; Holst, Jens J.; Svane, Maria S.; Madsbad, Sten (Frontiers in Nutrition, 2022)
Background and aims The metabolic consequences after Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) are often studied using a liquid mixed meal. However, liquid meals may not be representative of the patients’ everyday diet. We therefore examined postprandial glucose and gut hormone responses using mixed meals differing only with respect to meal texture. Methods Twelve RYGB-operated, 12 SG-operated, and 12 unoperated individuals (controls) were enrolled in the study. Participants were matched on age, sex, and body mass index. In randomized order, each participant underwent a liquid and a solid 4-h mixed meal test on separate days. The meals were isocaloric (309 kcal), and with identical macronutrient composition (47 E% carbohydrate, 18 E% protein, 32 E% fat, and 3 E% dietary fibers). The liquid meal was blended to create a smooth liquid texture while the other meal retained its solid components. Results Postprandial glucose concentrations (peak and incremental area under curve, iAUC) did not differ between the two meal textures in any group. In the control group, peak C-peptide was higher after the liquid meal compared with the solid meal (p = 0.04), whereas iAUCs of C-peptide were similar between the two meals in all groups. Peak of glucagon-like peptide-1 (GLP-1) was higher after the liquid meal compared with the solid meal in RYGB- and SG-operated individuals (RYGB p = 0.02; SG p < 0.01), but iAUC of GLP-1 did not differ between meal textures within any group. Peak of glucose-dependent insulin tropic polypeptide (GIP) was higher after the liquid meal in the SG and control groups (SG p = 0.02; controls p < 0.01), but iAUCs of GIP were equal between meals. There were no differences in total AUC of ghrelin between the liquid and solid meals within any of the groups. Conclusion A liquid and a solid meal with identical macronutrient composition result in similar postprandial glucose responses, both in operated and unoperated individuals. Small differences were observed for the postprandial peaks of C-peptide, GLP-1, and GIP concentrations. Overall, a liquid meal is suitable for evaluating glucose tolerance, β-cell function, and gut hormones responses, both after RYGB and SG and in unoperated individuals. Clinical Trial Registration [www.clinicaltrials.gov], identifier [NCT04082923].